2015
DOI: 10.5817/cpr2015-1-10
|View full text |Cite
|
Sign up to set email alerts
|

Features of chlorophyll fluorescence transients can be used to investigate low temperature induced effects on photosystem II of algal lichens from polar regions ( Short Communication )

Abstract: Chlorophyll fluorescence is an effective tool for investigating characteristics of any photosynthesizing organisms and its responses due to different stressors. Here, we have studied a short-term temperature response on three Antarctic green algal lichen species: Umbilicaria antarctica, Xanthoria elegans, and Rhizoplaca melanophtalma. We measured slow chlorophyll fluorescence transients in these Antarctic lichen species during slowely cooling of thallus temperature from 20°C to 5, 0 and-5°C with 20 minute accl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…In addition to Rfd values, a complete analysis of the slow phase of chlorophyll fluorescence transients (OPSMT) can be potentially used as indicators of freezing stress in photosynthetic apparatus (Mishra et al, 2015). Apart from thermic stress, it has been previously reported that Rfd is more sensitive to a variety of stress factors than Fv/Fm.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Rfd values, a complete analysis of the slow phase of chlorophyll fluorescence transients (OPSMT) can be potentially used as indicators of freezing stress in photosynthetic apparatus (Mishra et al, 2015). Apart from thermic stress, it has been previously reported that Rfd is more sensitive to a variety of stress factors than Fv/Fm.…”
Section: Discussionmentioning
confidence: 99%
“…Among a wide spectrum of methods using chlorophyll fluorescence technique in higher plants, slow (Kautsky) chlorophyll fluorescence transient has been used much less frequently then ´traditional´ parameters such a e.g potential (F V /F M ) and effective quantum yield of photosynthetic processes in photosystem II ( PSII ) -Bolhar-Nordenkamf et Oquist (1993). However, complex analysis of ChlF transient was presented by for Arabidopsis thaliana (Mishra et al 2014), and Antarctic lichens (Mishra et al 2015). The latter study suggested usefulness of ChF transient analysis to discriminate physical effects of low temperature on lichens and individual species responses, their tolerance and/or avoidance mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In lichens, slow ChlF transient was used to characterize sensitivity to photoinhibition (e.g. Conti et al 2014) and freezing stress (Mishra et al 2015). Similarly, Nabe et al (2007) studied sorbitol effect on shape of PSMT phase of transient in a liverworth (Marchantia polymorpha) and a moss (Bryum argenteum ).…”
Section: Introductionmentioning
confidence: 99%
“…Fast chlorophyll fluorescence measurement is a useful tool for non-invasive detection of various stress effects, such as e.g. high temperature , Martinazzo et al 2012, low and freezing temperature (Mishra et al 2015), drought (Oukarroum et al 2007 or heavy metal soil contamination (Żurek et al 2014). The chlorophyll fluo-rescence parameters change with different stresses.…”
Section: Introductionmentioning
confidence: 99%
“…It decreases PS II photochemical efficiency and modifies the values of chlorophyll fluorescence parameters (Smethurst et al 2005). Under the low temperature stress a variable chlorophyll fluorescence is decreased as well as photochemical quenching and effitiency of open PS II reaction centers (Yang et al 2007, Mishra et al 2015. Non-photochemical quenching of absorbed excitation energy increases with decreasing temperature.…”
Section: Introductionmentioning
confidence: 99%